The Incorporation of the 4C Skills in the Lesson Plans of Grade Eight - Luthfi, Nadia; Agustina, Imas Wahyu; Pujiati, Hanip (STAIRS: English Language Education Journal, 2023)
This research aimed to investigate the incorporation of the 4C skills in the lesson plans and to analyze how the 4C skills were implemented into the lesson plans of English for grade eight. The data for this qualitative content analysis research was gathered by analyzing ten lesson plans for grade eight of junior high school in Bekasi and Jakarta. The research found that all the lesson plans included all the 4C skills, which comprised 51% of communication skills, 69% of collaboration, 61% of critical thinking, and 69% of creativity. As the most widely incorporated, collaboration and creativity were found in learning and assessment activities. These findings are expected to be a recommendation for scholars, especially English teachers in designing lesson plans that meet 21st-century skill needs.